(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This paper explores the integration of assistive technologies into smart home interior design to enhance the quality of life for people with disabilities. It discusses how intelligent systems—such as voice-controlled devices, automated lighting, smart furniture, and environmental control units—can be harmoniously incorporated into interior design without compromising aesthetic and functional values. The study emphasizes the importance of inclusive design principles that prioritize accessibility, independence, and comfort. Furthermore, it highlights case studies and innovative approaches where interior spaces are customized to meet the physical, sensory, and cognitive needs of individuals with various types of disabilities. By bridging technology and design, smart homes can create a safer, more empowering environment for all users.